Household Solid Waste Management (HSWM) Awareness and Applications: A Comparative Study on Urban and Rural Sustainable Practices - Clarissa P. D. Castin; Rodrigo D. C. Dalmacio; Celine D. S. Flores; Betina M. M. Lamug; Joshua A. Manuevo (International Journal of Environment, Engineering and Education, 2022)
Solid Waste Management has been a problem for rural and urban communities. The study aims to provide a basis for urban and rural communities to improve their awareness, attitudes, and practices on solid waste management at a household level and collaborate with local government units toward effective Household Solid Waste Management (HSWM) implementation, ordinances, and mitigation. A 30-item close-ended assessment with 5-item follow-up questions was constructed to determine and compare the level of awareness, attitudes, and practices on HSWM between Barangay Bignay, Valenzuela (urban group), and Barangay Santa Elena, Hagonoy (rural group). The data was analyzed using One Way Analysis of Variance (ANOVA) to know the significant relationship between the bases (i.e., awareness, attitudes, and practices) in both barangays. Findings showed that the awareness of HSWM, practices, and attitude was high in the urban area, having a p-value of 0.003474, a lesser p-value than in rural with 0.007341. The comparisons analyzed using ANOVA reflecting a p-value of 0.96 concluded that there is a significant difference between the bases on the two groups since it is greater than the 0.50 level of significance. The bases were determined to have a positive relationship and thus directly affect the respondents' applications on HSWM and their communities. The LGUs implement an SWM program but still needs improvement as these contradict the measured practices. The study suggests a stricter implementation and orientation for both barangays on solid management programs.